Rational and practical aspects of Halal and Tayyib in the context of food safety. (January 2018) - Alzeer, Jawad; Rieder, Ulrike; Hadeed, Khaled Abou
Abstract: Background: Food plays a very important role in our daily life and most foods are based on regional, cultural and religious influences. Halal (permissible) food is emerging as one of the most important issue in food industries. Rational understanding of Halal, Tayyib (pure) and Khabith (impure) and their relationship with food safety is essential in determining Halal food status. Scope and approach: Initially Halal food was thought to be free from alcohol and pork. Later on Tayyib was strongly introduced into Halal food production and led to include food safety requirements as part of Halal food certificates. However, the practical description of Tayyib and the rational merging with Halal have not been well clarified yet. In this context, we would like to give a practical overview of Halal, Tayyib and Khabith concepts, their values and relationship to food safety. Key findings and conclusion: The rational understanding of Halal, Tayyib and Khabith in the context of food safety is essential. Considering Halal as a subject and Tayyib as a process, facilitates Halal certification procedure. The main objective of Tayyib is to produce clean and pure, food and to create a comfortable feeling as a main goal, which can be achieved if food is produced according to Sharia (Islamic principles). Halal labelled food should reflect the concept of Halal and Tayyib, particularly the identification of all ingredients involved in the production, determination of Halal and toxicity status, and removal of repulsive, Najis (ritually unclean) and toxic ingredients. Highlights: The relation between Food Safety and Halal Food is investigated. Integrating Tayyib into Halal is essential for Halal certification. Viewing Halal as a subject and Tayyib as a process clarify the practical relation between Halal Food and Food Safety. Main objectives and goal of Tayyib is to satisfy food safety requirement and achieve comfortable feeling when food is taken. Halal label reflects clean and safe food that is in compliance with Sharia.